2022
DOI: 10.1186/s12879-022-07284-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gender, age and vaccine on reactogenicity and incapacity to work after COVID-19 vaccination: a survey among health care workers

Abstract: Background The aim of our study was to assess the impact the impact of gender and age on reactogenicity to three COVID-19 vaccine products: Biontech/Pfizer (BNT162b2), Moderna (mRNA-1273) and AstraZeneca (ChAdOx). Additional analyses focused on the reduction in working capacity after vaccination and the influence of the time of day when vaccines were administered. Methods We conducted a survey on COVID-19 vaccinations and eventual reactions among 7… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 29 publications
2
30
1
Order By: Relevance
“…It is important to note that the frequency of adverse events was lower than that observed in the general population and no patients required medical support [12-]. However, the median age of the sample analyzed in the present work was higher and the effect of age on reactogenicity has already been described in previous studies [4-,5-,42-]. Moreover, in a Polewska’s (2021) study, adverse events were less frequently observed in dialyzed patients than in the age and sex-matched control group [39-].…”
Section: Discussionmentioning
confidence: 51%
“…It is important to note that the frequency of adverse events was lower than that observed in the general population and no patients required medical support [12-]. However, the median age of the sample analyzed in the present work was higher and the effect of age on reactogenicity has already been described in previous studies [4-,5-,42-]. Moreover, in a Polewska’s (2021) study, adverse events were less frequently observed in dialyzed patients than in the age and sex-matched control group [39-].…”
Section: Discussionmentioning
confidence: 51%
“… 16 In a study done in Germany, to report the incidence of adverse effects following vaccination with one of COVID-19 vaccines among HCWs, headache, chills and fever were also more common in women. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Age and gender might affect the reactogenicity to COVID-19 vaccination [ 14 , 15 , 34 ]. Using multivariate analyses, we investigated possible confounders.…”
Section: Discussionmentioning
confidence: 99%